Analisis Prosedur Pembelian Barang Di Bagian Purchasing Pada PT.XYZ (Studi Kasus Pada Perusahaan Kabel Di Kabupaten Karawang) - Alpiah, Alpiah; Nopiana, Medi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The manufacturing industry for cable manufacturers has a demand that continues to increase every year due to technological developments. Cables that have a function as a transmission medium that plays a role in the process of conveying information or fast data transfers make demand continue to increase. Purchasing is a basic activity of the company because without purchasing it is of course unable to meet demand so that the company's production or operational processes cannot run smoothly. The purpose of this research is to analyze the procedures for purchasing goods in the purchasing department at PT ZYZ and the obstacles encountered during purchasing activities so that later the author can provide solutions. This study used a qualitative descriptive method with triangulation (combined) data collection techniques, namely interviews and observation. The types of data sources are primary data obtained from direct research and secondary data obtained through articles, books, internet media or other literature. The research was conducted at PT XYZ, a cable company in Karawang regency. From the research that has been carried out, it is found that the purchasing procedure carried out by PT XYZ is quite good and structured, starting from receiving requests for goods until the goods are received by the warehouse department. PT XYZ itself consists of five purchasing categories, namely consumables, spare parts, services, packaging and raw materials. This purchasing activity is certainly inseparable from the problems or obstacles faced by the purchasing department during the purchasing process, for example, goods received are not as ordered, late arrival of goods, and damaged goods.